Chinese Education at Confucius Institutes in Belgium: A Pedagogical and Socio-Cultural Perspective - Song, Meng; Sercu, Lies (Dutch Journal of Applied Linguistics, 2023)
This poster presents the overview and the first step of the PhD project Chinese Education at Confucius Institutes in Belgium: A Pedagogical and Socio-Cultural Perspective. In recent decades, the enhanced globalization (Badwan, 2021) and mobility (McWilliams, 2008) have increased the complexity in foreign language classrooms in multilingual contexts (Bonnet & Siemund, 2018). It is thus worthwhile to explore the dynamics among diverse pedagogical and socio-cultural factors in real-life practices of foreign language education. Situating this issue in Belgium, this project investigates Chinese as a foreign language (CFL) education at local Confucius Institutes (CIs), aiming to provide insights into educational approaches at CIs as designed; delivered and received by different stakeholders (administrators, teachers, and learners).In the sections of Project Overview and Research Design of the poster, the key information on the project is summarized. First of all, Research questions identify the scope of the research, probing mainly in the following directions:• What are the gaps between actual local educational practices at CIs in Belgium and CIs’ official educational objectives?• To what extent does the teaching of CFL at CIs reflect Belgian learners’ socio-cultural backgrounds?• What are the pedagogical and managerial practices exerted at CIs in Belgium?• How do these pedagogical and managerial practices interact with local socio-cultural contexts?It is evident from the Research questions that the project mainly focuses on the potential misalignment between official objectives and on-site practices of management, teaching, and learning at CIs in Belgium, as well as the interplay of local socio-cultural factors (e.g., language conflicts, language ideology) in such educational contexts.In regard to Methodology, a mixed methods approach is chosen for data collection, in order to tackle the research questions from both qualitative and quantitative perspectives. A variety of data collection instruments including interviews, classroom observations, and a survey questionnaire are applied among three main target groups, namely, administrators, CFL teachers, and CFL learners at CIs in Belgium.The section on Research design then synthesizes the key information of the project in a multilayered structure. At the outer layer, the official objectives of CIs are examined through document analysis. The inner layers of Administrators, Teachers, and Learners are then studied by employing fitted data collection instruments, with the foci on the status quo and the relevant socio-cultural factors. For example, the target group of teachers triggers the research on local socio-cultural contexts of CFL teaching, and the current teaching methods and classroom practices conducted by the CFL teachers at CIs in Belgium. Hence, interview and classroom observation data are collected to analyze these aspects.The next section on First Step of the Project provides general information on the initial systematic review of the project, which is a review of post-2010 literature on the administration at CIs around the globe. In the total research project, it is situated at the inner layer of Administrators of Research Design, acting as a preparatory study for the empirical research on administrators at CIs in Belgium, in order to tackle Research question ① and ③. The aim of this systematic review is to examine the actual managerial practices at CIs in different areas, especially regarding the misalignment of CIs’ official objectives in local institutions. The article selection routine follows the PRISMA guidelines (Page, M. J. et al., 2021) with “Confucius Institutes/CIs” as the search term. 347 articles were selected with research foci in seven categories and cases from 46 countries/regions.Relevant contents of the selected articles are then extracted for Thematic analysis, based on which a Coding tree of themes with three levels of generalization is constructed in the section of Present Findings. Level 1 of the coding tree is developed from the research aim of the systematic review, namely, to map CIs’ official status (Overview of CIs' management) and CIs’ actual managerial practices (successes, problems, and suggestions), which are then deconstructed. The practical sides of CIs’ management are categorized in the three most relevant aspects of Management, Education, and Intercultural communication at Level 2. Themes for further analysis surface at Level 3 and stand for the most prominent messages of the upper-level categories. For instance, the Level 3 theme “Lack of local socio-cultural concern” reflects one aspect of key information of the Level 1 and Level 2 categories “Problems of CIs' management – Management”.Finally, the Conclusion section of the poster states the strengths of the research project and the next step following the first step. The project is encompassing educational research collecting data from multiple sources, and the output might improve the localization of CFL education and intercultural understanding of such global educational institutions. The ensuing step of the project will be the systematic reviews of the other two target groups of teachers and learners as well as their practices at CIs.